Factors affecting the performance of the University of the Philippines Institute of Library and Information Science graduates (1992-2004) in the licensure examination for librarians - Noor Azman, Norman S.; Faderon, Rosalie B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2005)
This study aims to determine the predictors of success of ILIS graduates in the Licensure Examination for Librarians. Purposive sampling was used. Data gathered through questionnaires and document analysis.
Six factors correlated with the graduates' performance in the licensure examination: 1) Weighted average in Library and Information Science courses; 2) Curriculum Weighted Average; 3) Date of Examination; 4) Date of graduation; 5) Mode of Entry; and 6) Age Performance in the specific subjects of the licensure examination was correlated with performance in the corresponding academic subjects except for Selection and Acquisition.
Students are advised to study hard and do well in all academic subjects, especially in major subjects, to increase the likelihood of success in the licensure examination. The Institute must strengthen its admission and academic programs, particularly, Selection and Acquisition and Indexing and Abstracting to achieve 100 percent performance in the licensure examination.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Librarians -- Philippines; University of the Philippines Institute of Library and Information Science -- Alumni and Alumnae